THE JURY AND ASSESSMENT OF EVIDENCE BASED ON FREELY JUDICIAL BELIEFS - Bugarski, Tatjana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
In modern criminal procedural legislation, the great attention is paid to the issue of collecting evidence i.e. evidentiary actions as one of the most important issues of criminal proceedings. In most cases, the processing and analysis of this issue comes down to conditions for the application of evidentiary actions, proceedings authorities, the manner of their performance etc. However, the question of the assessment of evidence based on freely judicial beliefs remains as one of the most important questions concerning evidentiary actions, which has an impact on the outcome of the proceedings and the court’s decision. This issue is particularly important when one takes into account the existence of the court traditional laic elements within the general criminal proceedings. Therefore the subject of this paper is the assessment of evidence based on juror’s freely judicial beliefs, their role in criminal proceedings, their powers and competences, as well as the question of justification of their participation in criminal proceedings.